Comparative Study of Local Wisdom of the Built Environment between Sasak Senaru Architecture, Lombok, Indonesia and Jeju Architecture, Korea. (International Conference of Graduate School on Sustainability (ICGSS), 2020)
Comparative Study of Local Wisdom of the Built Environment between Sasak Senaru Architecture, Lombok, Indonesia and Jeju Architecture, Korea. Lee Jung Ho *, Junianto Hadiwiryono, Dina Poerwoningsih Magister of Architecture, Graduate School, University of Merdeka Malang *e-mail: mrnta@daum.net   Much local wisdom is studied in order to find patterns of resistance to change and a sustainable built environment. These patterns will vary in the form of architectural diversity of a nation, influenced by climatic and geographic factors that are also related to socio-economic and socio-cultural aspects. This study aims to analyze the similarities and differences in responding to climate and geography as well as spatial design through a comparison of the traditional Sasak Senaru residential area of ​​Lombok, Indonesia and the traditional residential space of Jeju, Korea. The two different forms of traditional architecture were chosen to represent their respective existence in different climatic and geographic backgrounds, but they have similar performances. This research is also based on a thesis about the relationship between architecture, humans and the environment that applies generally and universally, especially in traditional architecture. Researchers used qualitative research methods. The results of the study found similarities in efforts to respond to climate, in ways that are similar but different in the purpose of specific comfort in the built environment. Traditional settlements in Lombok are only used as shelter, while on Jeju Island they are used as shelter from the weather. Both forms of architecture use materials from nature to make housing, such as stone, wood, bamboo, soil, and grass or straw. Another result is in spatial arrangement which indicates differences in function and space requirements. The layout of the Sasak Senaru architectural residential space is dominated by ritual / customary needs for communal interests. Meanwhile, Jeju architectural residences prioritize residential privacy. Jeju people respect individual life more, so individual buildings are more important than communal buildings. Another difference is seen in the layout of the communal space. Sasak Senaru architecture shows a hierarchy of spaces according to social class in society. Meanwhile, in Jeju architecture, there are no social class differences in the arrangement of the settlements. Keywords: Sustainability of the built environment, Sasak Senaru Architecture, Jeju-Korea architecture, local wisdom